La informalidad y evasión tributaria en las bodegas del AA HH Bello Horizonte de San Juan Bautista al tercer trimestre 2021 - Ushiñahua Urquia, Justa (2022)
The general objective of the study was to determine the relationship between informality and tax evasion in the AA.HH. Bello Horizonte de San Juan Bautista, in the third quarter of 2021, choosing for an applied research and non-experimental design, where 14 merchants from said settlement were taken as a sample, the survey technique and the questionnaire instrument were used to collect information. information, since it was concluded that informality is very low (43%), since merchants never issue receipts when making a sale, likewise, lack of trust is always a factor for failing to pay taxes, in addition, they never have security cameras in their facilities, too, have never attended training to improve their business skills. On the other hand, very low tax evasion (50%), since they never know the dates for the payment of their taxes, and they do not participate in training, as well as they never opt for the electronic means of payment for their products, but they always they welcome a regime that allows them to pass as small taxpayers. Finally, it has been determined that there is a relationship between informality and tax evasion, approved with a significance of 0.000 and a Spearman's Rho correlation of 0.904, being very strong positive.